2002
DOI: 10.1128/jvi.76.1.364-378.2002
|View full text |Cite
|
Sign up to set email alerts
|

The Interacting UL31 and UL34 Gene Products of Pseudorabies Virus Are Involved in Egress from the Host-Cell Nucleus and Represent Components of Primary Enveloped but Not Mature Virions

Abstract: A 2.6-kbp fragment of the pseudorabies virus (PrV) genome was sequenced and shown to contain the homologues of the highly conserved herpesvirus genes UL31 and UL32. By use of a monospecific antiserum, the UL31 gene product was identified as a nuclear protein with an apparent molecular mass of 29 kDa. For functional analysis, UL31 was deleted by mutagenesis in Escherichia coli of an infectious full-length clone of the PrV genome. The resulting virus mutants were deficient in plaque formation, and titers were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
289
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(310 citation statements)
references
References 65 publications
17
289
4
Order By: Relevance
“…Previous studies have shown that pUL50 and pUL53 interact with each other and form a complex at the nuclear rim, with pUL50 appearing to direct the complex to this location (Milbradt et al, 2007; Camozzi et al, 2008). Similar results were obtained for their homologues in other herpesviruses (Reynolds et al, 2001;Fuchs et al, 2002;Farina et al, 2005). Furthermore, the interaction network comprises multiple interactions between pUL50, pUL53 and p32, as well as a viral and a cellular protein kinase (i.e.…”
supporting
confidence: 70%
“…Previous studies have shown that pUL50 and pUL53 interact with each other and form a complex at the nuclear rim, with pUL50 appearing to direct the complex to this location (Milbradt et al, 2007; Camozzi et al, 2008). Similar results were obtained for their homologues in other herpesviruses (Reynolds et al, 2001;Fuchs et al, 2002;Farina et al, 2005). Furthermore, the interaction network comprises multiple interactions between pUL50, pUL53 and p32, as well as a viral and a cellular protein kinase (i.e.…”
supporting
confidence: 70%
“…Despite these findings, pUL34 and pUL9 are unlikely to play significant roles during retrograde transport of HSV-1. Neither is present in mature HSV-1 virions [55,56], and pUL34 is not found in mature virions of the related PrV [57][58][59]. Furthermore, deletion of the UL34 gene does not prevent infection of cells by HSV-1 [60].…”
Section: Dynein Cofactor: Dynactinmentioning
confidence: 99%
“…The unique short genome region contains a cluster of six conserved alphaherpesvirus genes encoding membrane proteins, including gB, gC, gG, gJ, gM and gN [32]. The gG gene US4 has been predicted to form a coterminal transcription unit with the translocated UL47 gene of ILTV [32], and were only found in infected cells [8,27]. The differentiation of vaccine and ''wild-type'' ILT viruses based on sequencing of UL47 and glycoprotein G genes could serve as a useful tool for future investigations [22].ILTV infection causes respiratory disease symptoms in chickens, pheasants, partridges, and peafowl [5,13].…”
Section: Introductionmentioning
confidence: 99%